Gadolinium-Associated Acute Kidney Injury: A 10-Year Single-Center Retrospective Cohort Study - Ariyanopparut, Saravanee; Meenune, Wanniya; Srisakorn, Ponprom (Journal of the Nephrology Society of Thailand, 2025)
Background: In studies conducted in Europe and the United States, gadolinium-associated acute kidney injury (GA-AKI) has been reported in high-risk patients after receiving gadolinium-based contrast agents (GBCAs). Currently, there is no data available on Asian populations to confirm these findings. Methods: A retrospective cohort study of chronic kidney disease patients with an estimated glomerular filtration rate (eGFR) ≤ 60 ml/min/1.73m2 who received GBCAs from 2013 to 2023 at a tertiary care hospital. The outcomes were the incidence of GA-AKI and the associated risk factors. Results: Among the 182 patients, the incidence of GA-AKI was 4.4%. Although the GA-AKI group had significantly higher age (> 65 years) (OR 6.374; 95% CI 0.720-56.426, p=0.096), diastolic blood pressure > 80 (OR 6.148; 95% CI 1.111-34.008, p=0.037) and eGFR ≤30 ml/min/1.73m2 (OR 7.920; 95% CI 1.642-38.196, p=0.010). The ROC curve analysis for predicting GA-AKI scored 2 out of 3, with a sensitivity of 87.5% and a specificity of 78.2%. Conclusions: The incidence of GA-AKI was low. The associated factors included older age, higher diastolic blood pressure, and eGFR ≤ 30 ml/min/1.73m2.